Twelve O'Clock High - Henry, King.; Dean, Jagger; Gary Merrill; Hugh Marlowe; Millard Mitchell; Paul Stewart; Robert Arthur; Gregory Peck (USA Twentieth Century-Fox Film Corporation, 1949)
In this story of the early days of daylight bombing raids over Germany, General Frank Savage must take command of a ""hard luck"" bomber group. Much of the story deals with his struggle to whip his group into a diciplined fighting unit in spite of heavy losses, and withering attacks by German fighters over thier targets. Actual combat footage is used in this tense war drama.
A hard-as-nails general takes over a bomber pilot unit suffering from low morale and whips them into fighting shape.
Sy Bartlett
Language : Turkish
Subtitles : English, Turkish, Hebrew
Keywords: War; Drama